ANALISIS SISTEM KOMPENSASI BERBASIS JOB VALUE PADA UMKM STUDI KASUS : PT XY DI DEPOK, JAWA BARAT - Mohamad Rifqi Arief Syafruddin; Dea Ayu Saputri; Vivi Laelatuz Zahro; Nur Ashri Putri Zega; Mita Sugiarti (STIE DWI SAKTI BATURAJA, 2022)
The establishment of an effective compensation system is an important part of human resource management because it helps attract and retain talented jobs. Compensation is all income in the form of money, goods directly or indirectly received by employees in return for services provided to the company. The object of this journal research is PT XY which is one of the book distribution companies located in the Depok area, West Java. The purpose of this study is to identify the condition of the compensation system applied, identify compensable factors to be analyzed, and analyze the ideal compensation system to be applied which will then be the basis for a survey of workers' decent living needs (KHL) at PT XY. The data used in this study is primary data. The primary data collection technique was in the form of interviews through electronic communication media, namely Zoom and Whatsapp as a medium for giving questionnaires. This research is a quantitative and qualitative research by describing the compensation system applied at PT XY.